2014
DOI: 10.1371/journal.pone.0101023
|View full text |Cite|
|
Sign up to set email alerts
|

Helminth Induced Suppression of Macrophage Activation Is Correlated with Inhibition of Calcium Channel Activity

Abstract: Helminth parasites cause persistent infections in humans and yet many infected individuals are asymptomatic. Neurocysticercosis (NCC), a disease of the central nervous system (CNS) caused by the cestode Taenia solium, has a long asymptomatic phase correlated with an absence of brain inflammation. However, the mechanisms of immune suppression remain poorly understood. Here we report that murine NCC displays a lack of cell surface maturation markers in infiltrating myeloid cells. Furthermore, soluble parasite li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
3
20
0
Order By: Relevance
“…Previous studies have suggested that increased intracellular calcium plays important roles in mediating the TLR-triggered immune response. [35][36][37][38][39][40][41][42][43][44][45][46][47] In most studies, attention has been paid to intracellular calcium mobilization. However, TLRs may trigger calcium release from the ER and then STIM-ORAImediated calcium entry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that increased intracellular calcium plays important roles in mediating the TLR-triggered immune response. [35][36][37][38][39][40][41][42][43][44][45][46][47] In most studies, attention has been paid to intracellular calcium mobilization. However, TLRs may trigger calcium release from the ER and then STIM-ORAImediated calcium entry.…”
Section: Discussionmentioning
confidence: 99%
“…A long asymptomatic period, marked by the absence of local inflammation, usually follows the parasite establishment in the CNS . When parasite and/or host signals trigger the inflammatory response, symptoms commence with the ensuing damage of both peripheral and central cysticerci in pigs and humans .…”
Section: Inflammation and Host Factorsmentioning
confidence: 99%
“…These findings favor the view that activation of TRPC1 is required for the host defense against bacterial infections through the TLR4-TRPC1-PKCα signaling pathway, but its excessive activity may lead to exacerbation of inflammation [32]. A similar but in-opposite-direction involvement of TRPC1-mediated Ca 2+ entry in TLR-mediated inflammation has been demonstrated in microglia and macrophages from m i c e i n t r a c r a n i a l l y i n o c u l a t e d w i t h a h e l m i n t h Mesocestoides corti [33,34]; it has been known that humans infected with a related helminth cestode Taenia solium have immunosuppressive rather than inflammatory responses in the asymptomatic phase after the infection. Experiments using It should be noted that appropriate operation of autophagy is essential to suppress the caspase-1 activity, which would prevent the production of inflammatory cytokine (IL-1β and IL-18).…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 81%
“…One of the factors known to activate NF-κB is an elevation in [Ca 2+ ] i [100,101]. There are several papers linking Ca 2+ -permeable TRP channels to NF-κB-mediated inflammatory reactions; suppression of TRPC1-mediated Ca 2+ entry inhibited NF-κB activation, which is associated with immunosuppressive mechanism in helminth infections [34]; pharmacological inhibition of TRPM7 channel suggested its involvement in LPS-induced EC migration via the TLR-NF-κB signaling [37]; endotoxininduced lung injury involves TLR4-mediated NF-κB activation in a manner dependent on TRPC6-mediated Ca 2+ entry [21].…”
Section: Nf-κbmentioning
confidence: 99%